biokonservasi.id: A Development of a Conservation Education Website in the Mount Ciremai National Park as a Learning Resource - Bambang Ekanara; Ina Rosdiana Lesmanawati; Dede Cahyati Sahrir; Ilma Riksa Isfiani; Nguyen Thuy Dung (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
The development of science and technology is inevitable, therefore innovation is needed in every aspect of education to keep up with technological advances, as well as conservation education. This research was conducted with the aim of exploring the environmental service potential of Mount Ciremai National Park (TNGC) by developing a TNGC conservation education website. The TNGC conservation education website to support environmental awareness was developed using the Research and Development (RD) research method. Using the Four-D model which is carried out until the disseminate stage. At the design stage, the Multimedia Development Life Cycle (MDLC) method was used because the TNGC conservation education website is a multimedia product. Based on the results of the material and media expert test assessment, the TNGC conservation education website to support environmental awareness received an average score of 81.89, which means it falls into the feasible category. These results are obtained based on the results of data processing for material aspects of 81.47; and media aspects of 82.31. The development of this website media is expected to be one of the alternative learning resources for sustainable conservation education, especially within the Department of Biology and generally for the wider community.